What is 194 in radical form

Answers

Answer 1
Answer:

The radical form of 194 = √2 x √97

To find the radical form of 194,

we need to factorize it into its prime factors.

So, let's start by dividing 194 by the smallest prime factor, which is 2,

⇒ 194 ÷ 2 = 97

We can see that 97 is a prime number,

so we can't divide it any further.

Therefore, the prime factorization of 194 is,

⇒ 194 = 2 x 97

Now, we can write the radical form of 194,

⇒√194 = √(2 x 97)

We can simplify this expression by breaking it down into the product of two separate square roots:

⇒ √(2 x 97) = √2 x √97

⇒The radical form of 194 is √2 x √97.

To learn more about radical form visit:

brainly.com/question/29052172

#SPJ6

Answer 2
Answer: 194 in radical form is just √194. I don't believe any square roots go into it. Hope that helps. :)

Related Questions

The population of a species of rabbit triples every year. This can be modeled by f(x) = 4(3)^x and f(5) = 972. What does the 5 represent?
In the year 2000, there were 5,000 people living in the town of Clairmont. By 2010, the population had grown to 5,600. What is the percent of change in the population from 2000 to 2010?88.3% 11% 12% -20%
99.2 +99.8 ????? bg UwU
The cafeteria sells 498 cartons of milk and 246 bottles of juice every day how many total milk and juice containers are sold each day
Suppose the surface area of a sphere is 324π square units. What is the volume, in cubic units, of this sphereA) 9π B) 81π C) 324π D) 972π

| x - 42.04 | = 23.24

Answers

|x - 42.04| = 23.24
|x - 42.04| = ±23.24
|x - 42.04| = 23.04    U    |x - 42.04| = -23.04
  x - 42.04 = 23.04     U     x - 42.04 = -23.04
    + 42.04 + 42.04              + 42.04   + 42.04
              x = 65.05           U            x = 19

Assume that women's heights are normally distributed with a mean given by u = 64.3 in, and a standard deviation given by 0 = 2.7 in. (a) f 1 woman is randomly selected, find the probability that her height is less than 65 in. (b) if 43 women are randomly selected, find the probability that they have a mean heightless than 65 in. (a) The probability is approximately I. (Round to four decimal places as needed.) 4

Answers

Answer:

0.9533

Step-by-step explanation:

(a) Probability that a randomly selected woman's height is less than 65 inches:

Using the z-score formula:

=

Z=

σ

X−μ

Where:

X = 65 inches

μ = 64.3 inches

σ = 2.7 inches

=

65

64.3

2.7

0.2593

Z=

2.7

65−64.3

≈0.2593

Now, find the probability associated with this z-score, which is approximately 0.6010 (rounded to four decimal places).

(b) Probability that the mean height of 43 randomly selected women is less than 65 inches:

Using the Central Limit Theorem:

μ (mean of the sample means) remains 64.3 inches.

sample mean

σ

sample mean

 (standard deviation of the sample means) is calculated as

2.7

43

0.4115

43

2.7

≈0.4115.

Now, find the z-score for a sample mean of 65 inches:

=

65

64.3

0.4115

1.6924

Z=

0.4115

65−64.3

≈1.6924

The probability associated with this z-score is approximately 0.9533 (rounded to four decimal places).

A four-sided polygon has these properties of rotation and reflection:When it rotates 360°, it maps onto itself at four different angles of rotation.
It can be reflected onto itself across four different lines of reflection.
Which kind of polygon must it be?

Answers

A square of course fits the description.
it would be a square had some research

A number increased by seven is 15

Answers

Answer:

The number is 8.

To solve this equation, we can set it up as follows:

Let x be the unknown number.

  • The equation "A number increased by seven is 15" can be written as:

x + 7 = 15

  • Now, to find the value of x, we need to isolate it on one side of the equation. We can do this by subtracting 7 from both sides of the equation:

x + 7 - 7 = 15 - 7

  • On the left side, the +7 and -7 cancel out, leaving us with just x:

x = 15 - 7

  • Now, simplify the right side of the equation:

x = 8

So, the unknown number is 8.

To write the expression, I'll follow these steps :

↠ First, I am going to choose a letter that will represent my number.

↠ Then I'll plug it into the expression, and write the rest.

STEP ONE

  I'll choose d for my number.

STEP TWO

 We now have : d increased by 7 is 15, which is the same thing as d + 7 = 15.

To find d, subtract 7 from both sides :

d = 15 - 7 = 8

Therefore, d = 8.

What is the product of 2x + y and 5x – y + 3?

Answers

Answer:  The required product is 10x^2-y^2+3xy+6x+3y.

Step-by-step explanation:  We are to find the product f the following two algebraic expressions:

E_1=2x+y,\n\nE_2=5x-y+3.

To find the product of the above two expressions, we must multiply each term of the first expression with each term of the second expression.

The multiplication is as follows:

M\n\n=E_1 * E_2\n\n=(2x+y)*(5x-y+3)\n\n=10x^2-2xy+6x+5xy-y^2+3y\n\n=10x^2-y^2+3xy+6x+3y.

Thus, the required product is 10x^2-y^2+3xy+6x+3y.

Answer: 10x^2-y^2+3xy+6x+3y

Step-by-step explanation:

Given expressions are 2x+ y and 5x -y +3

Product of 2x+y and 5x-y+3 is

(2x+y)* (5x-y+3) = 2x* (5x-y+3) + y* (5x-y+3) ( by applying distributive property under multiplication over addition)

(2x+y)* (5x-y+3) = 10x^2-2xy+6x+5xy-y^2+3y (again by distributive property)

(2x+y)* (5x-y+3) = 10x^2-y^2+3xy+6x+3y  ( by operating the like terms.)

What is the additive inverse of the polynomial –9xy2 + 6x2y – 5x3?

Answers

Answer:

The additive inverse of given expression is 9xy^2-6x^2y+5x^3.

Step-by-step explanation:

The given polynomial is

-9xy^2+6x^2y-5x^3

Let a be any number and b is its additive inverse, then

a+b=0

b=-a

The value of b is equal to -a. It means the additive inverse of a is -a.

The additive inverse of given expression is

-(-9xy^2+6x^2y-5x^3)=9xy^2-6x^2y+5x^3

Therefore the additive inverse of given expression is 9xy^2-6x^2y+5x^3.

Additive inverse of 9xy² + 6x²y - 5x³

-1(9xy² + 6x²y - 5x³) ⇒ (-1)(9xy²) + (-1)(6x²y) + (-1)(-5x³)

-9xy² - 6x²y + 5x³ is the additive inverse of the given polynomial.